2023
DOI: 10.3389/fneur.2022.1081219
|View full text |Cite
|
Sign up to set email alerts
|

Non-motor symptoms in multiple system atrophy: A comparative study with Parkinson's disease and progressive supranuclear palsy

Abstract: BackgroundNon-motor symptoms (NMS) are compulsory clinical features for the clinical diagnosis of multiple system atrophy (MSA), some of which precede motor symptoms onset. To date, few studies have systematically investigated NMS in MSA and the timing of presenting NMS as the disease progresses. Clinically, MSA is difficult to be differentiated from Parkinson's disease (PD) and progressive supranuclear palsy (PSP), and the differences in NMS between MSA and PD/PSP remain unclear. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The literature on sex-related differences in the clinical presentation of MSA suggested that compared to men, women more frequently have a motor symptomatic onset and a better response to L-dopa, but overall develop greater motor disability over time and more frequently suffer from pain, depression, anxiety, sarcopenia, frailty, early falls, fractures, worse cognitive performance, and lower health-related quality of life [ 10 , 11 , 22 , 25 , 31 , 48 , 50 , 51 , 59 ]. By contrast, men were more frequently reported to have an autonomic symptomatic onset and to suffer from more widespread and severe autonomic failure, except for urinary urge incontinence and constipation, which were more common in women [ 10 , 12 , 20 , 34 , 36 , 37 , 41 , 51 , 55 , 60 , 61 ]. Higher supine BP levels as well as greater orthostatic BP falls were both associated with increased mortality in men with MSA [ 54 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on sex-related differences in the clinical presentation of MSA suggested that compared to men, women more frequently have a motor symptomatic onset and a better response to L-dopa, but overall develop greater motor disability over time and more frequently suffer from pain, depression, anxiety, sarcopenia, frailty, early falls, fractures, worse cognitive performance, and lower health-related quality of life [ 10 , 11 , 22 , 25 , 31 , 48 , 50 , 51 , 59 ]. By contrast, men were more frequently reported to have an autonomic symptomatic onset and to suffer from more widespread and severe autonomic failure, except for urinary urge incontinence and constipation, which were more common in women [ 10 , 12 , 20 , 34 , 36 , 37 , 41 , 51 , 55 , 60 , 61 ]. Higher supine BP levels as well as greater orthostatic BP falls were both associated with increased mortality in men with MSA [ 54 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature on sex-related differences in the clinical presentation of MSA primarily consisted of studies conducted following the publication of the second consensus MSA criteria [ 14 ]. Altogether, these studies indicated that women suffer from a greater motor disability and higher neuropsychiatric burden, while possibly experiencing a slight survival benefit due to initial motor onset and overall less severe autonomic failure compared to men [ 10 12 , 38 , 41 , 51 , 52 , 54 , 55 , 57 , 60 , 61 ]. A motor onset in MSA may positively impact women’s survival by prompting an earlier referral, diagnosis, and thus optimized care [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple system atrophy (MSA) is an intractable neurodegenerative disorder characterized by various combinations of parkinsonism, cerebellar ataxia, and autonomic failure, and the prevalence of MSA is 3–5/100000 in the general population [ 1 , 2 ]. Two main subtypes of MSA are MSA with predominant parkinsonism (MSA-P) and MSA with prominent cerebellar ataxia (MSA-C).…”
Section: Introductionmentioning
confidence: 99%